The Contribution of the Tahfidz Program in Building the Character and Spiritual Values of MIN 01 Bandung City Students: Kontribusi Program Tahfidz dalam Membangun Karakter dan Nilai Spiritual Siswa MIN 01 Kota Bandung - Hilmi, Fuad; Hidayatulloh, Deden Syarif (Journal of Society and Development, 2024)
Character education has a crucial role in basic education as an effort to build a generation that is intellectually intelligent and has noble character. This study aims to analyze the contribution of the Tahfidz program in building the character and spiritual values of students in MIN 01 Bandung City. A descriptive qualitative approach is used to explore experiences, views, and practices in the implementation of the Tahfidz program involving 5th grade students, teachers, and parents. The results of the study show that the Tahfidz program has a positive impact on student discipline, honesty, responsibility, and cooperation. The on-time attendance rate of students increased from 60% to 85% after the program was running, while the habit of self-reliance at home increased from 30% to 70%. In addition, group activities such as the Sima'an method help build student honesty and responsibility, where 90% of students carry out group tasks honestly and objectively. The cooperation created in the group also strengthens solidarity, where 80% of students actively help friends who are experiencing difficulties. This program has succeeded in instilling discipline and an orderly lifestyle and forming solid moral and spiritual values. This study recommends the integration of the Tahfidz program into the formal education system as an effort to build a young generation with high character and integrity.